2003
DOI: 10.1016/s0921-4534(02)02305-5
|View full text |Cite
|
Sign up to set email alerts
|

Gravitomagnetic field of a rotating superconductor and of a rotating superfluid

Abstract: The quantization of the extended canonical momentum in quantum materials including the effects of gravitational drag is applied successively to the case of a multiply connected

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
1

Year Published

2005
2005
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 18 publications
5
44
1
Order By: Relevance
“…For Niobium we get B g =3.9×10 -6 .ω rad.s -1 at T=0 K. This is nearly two orders of magnitude below a recently published conjecture by one of the authors, that a non-classical gravitomagnetic field could be responsible for a reported disagreement between the theoretically predicted and measured Cooper-pair mass of a rotating Niobium ring (Tajmar and de Matos, 2003;2006b). Although the values for the gravitomagnetic London moment are predicted to be small, compared to classical gravitomagnetic fields, e.g.…”
Section: Introductionmentioning
confidence: 49%
“…For Niobium we get B g =3.9×10 -6 .ω rad.s -1 at T=0 K. This is nearly two orders of magnitude below a recently published conjecture by one of the authors, that a non-classical gravitomagnetic field could be responsible for a reported disagreement between the theoretically predicted and measured Cooper-pair mass of a rotating Niobium ring (Tajmar and de Matos, 2003;2006b). Although the values for the gravitomagnetic London moment are predicted to be small, compared to classical gravitomagnetic fields, e.g.…”
Section: Introductionmentioning
confidence: 49%
“…In [51], Peng and Torr investigated the coupling of gravitational waves to superconductors, while Speliotopoulos found a cross-coupling term between the electromagnetic and gravitational field in the long-wavelength approximation, which could lead to a conversion between the two fields [52]. Tajmar and de Matos considered a classical coupling between electromagnetic and gravitoelectromagnetic waves 4 [53,54], which, however, would lead to a very small interaction strength (cf. Sect.…”
Section: Generation and Detection Of Gravitational Waves Via Quantum mentioning
confidence: 99%
“…The idea of Tajmar and de Matos [54,95] is the combination of two effects: the consideration of the London moment as well as the gravitomagnetic field caused by the rotation of a superconducting mass. To this end, they consider a superconductor rotated about its axis and include gravitational drag effects.…”
Section: Currently Proposed Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…• Experimentally explore gravitomagnetic fields in quantum materials [48]. Opportunities for continued research clearly exist on any of these options.…”
Section: Tests Of Podkletnov Claimmentioning
confidence: 99%